TRLFS study on the complexation of Cm(III) and Eu(III) with SO3-Ph-BTBP - Wagner, Christoph; Müllich, Udo; Geist, Andreas; Panak, Petra (Dalton transactions, 2015)
The complexation of Cm(III) and Eu(III) with a water soluble BTBP (sodium 3,3′,3′′,3′′′-([2,2′-bipyridine]-6,6′-diylbis(1,2,4-triazine-3,5,6-triyl))tetrabenzenesulfonate, SO3-Ph-BTBP) is studied using time resolved laser fluorescence spectroscopy. For the complexation of Cm(III) the influence of the medium (10−3 M HClO4 → 0.5 M HNO3) is investigated in detail revealing important impacts of the applied medium (pH, ionic strength, anions) on the speciation and conditional stability constants. SO3-Ph-BTBP forms 1 : 2 complexes with Cm(III) and Eu(III). The conditional stability constants of [Cm(SO3-Ph-BTBP)2]5− and [Eu(SO3-Ph-BTBP)2]5− in 0.5 M HNO3 are determined to be log β02 = 7.3 ± 0.3 and log β02 = 5.4 ± 0.5, respectively. The difference of 1.9 orders of magnitude is in line with hydrophobic BT(B)P type ligands and shows that the selectivity is not affected by tuning the hydrophilicity using SO3-Ph-side chains.